(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Landscape art design can not only enhance the beauty of the city, but also meet the growing needs of people’s spiritual civilization. With the acceleration of China’s urbanization construction process, higher requirements have been put forward for landscape design. In recent years, more and more fresh and trendy elements have been incorporated into the landscape design work, greatly enhancing the beauty of urban landscape, among which animation elements are a representative of modern elements into the landscape art design, injecting new vitality into the landscape art design work. We can see that more and more landscape art design at home and abroad began to use animation elements, its novel and unique design style is good to grab the public’s attention, so this paper mainly focuses on the analysis of the use of animation elements in landscape art design, in order to bring inspiration and inspiration to the majority of design workers.